Coconut Avenue, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A picture of a road lined with coconut trees.
Colour: Sepia; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago